1995
DOI: 10.1007/bf00222929
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selection for sodium transport and of selection for agronomic characteristics upon salt resistance in rice (Oryza sativa L.)

Abstract: A multiple cross was constructed with the aim of combining component traits for the complex salinity resistance character. The aim was to combine donors for physiological traits with the agronomically desirable semidwarf/intermediate plant type and with the overall salinity resistance of the traditional tall land races. We report a study of selection strategies in the resulting breeding population. The effects of early selection for agronomic traits and early selection for low sodium transport were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 11 publications
2
29
0
2
Order By: Relevance
“…Our results are one of the first rigorous assessments of the heritability of quantitative physiological traits involved in the tolerance of salinity. The finding that sodium transport in rice has a narrow-sense heritability of over 0-4 supports the view that selection for low sodium transport is feasible (Yeo 1992;Garcia et al 1995). The data are in close agreement with results for japonica rice obtained by a different methodology (diallel analysis) where narrow-sense heritabiiities of 0-49 (sodium), 0-53 (potassium) and 0-51 (sodium to potassium ratio) were found (Lee 1995).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our results are one of the first rigorous assessments of the heritability of quantitative physiological traits involved in the tolerance of salinity. The finding that sodium transport in rice has a narrow-sense heritability of over 0-4 supports the view that selection for low sodium transport is feasible (Yeo 1992;Garcia et al 1995). The data are in close agreement with results for japonica rice obtained by a different methodology (diallel analysis) where narrow-sense heritabiiities of 0-49 (sodium), 0-53 (potassium) and 0-51 (sodium to potassium ratio) were found (Lee 1995).…”
Section: Discussionsupporting
confidence: 85%
“…Significant differences in the frequency distribution of sodium transport were evident after three cycles of repeated selection (differences after the first and second cycles may have been obscured by variability) and lines segregated further in the fourth and fifth cycles of selection. Gregorio & Senadhira (1993) and Garcia et al (1995) both concluded that selection in breeding populations designed for salinity tolerance should be delayed because traits are not fixed in the early generations. We carried out the heritability measurements at generations in which the material would slill be segregating for sodium transport but in which variability had decreased sufficiently to allow estimation of line means; we assessed the single cross (1R55I78) at F4/F, and the multiple cross {IR59462) at FS/F4.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…These phases could be correlated with several mechanisms. Several biochemical pathways, ion and metabolite transport processes, hormonal control, cell structure and organ growth, and signaling have been identified (Yeo et al, 1990;Flowers and Yeo, 1995;Garcia et al, 1995;Price et al, 1997;Hasegawa et al, 2000). It is not possible to correlate the physiological terms and only partially understood mechanisms in the context of this microarray analysis of plant salinity stress.…”
Section: Distinguishing Response Categories In Salt-sensitive and Salmentioning
confidence: 99%